Предмет: Алгебра,
автор: anelkakaramelka72
3а+2/а²-2а+1 - 6/а²-1 - 3а-2/а²+2а+1 как сделать?? Пж пж пж решит ПЛИИИИИЗ
Ответы
Автор ответа:
1
Ответ:
Объяснение:
(3a+2)/(a-1)² - 6/(a-1)(a+1) - (3a-2)/(a+1)²= ((3a+2)*(a+1)²-6(a²-1)-(3a-2)*(a-1)²)/(a²-1)²= (3a³+8a²+7a+2-6a²+6-3a³+8a²-7a+2)/(a²-1)²= (10a²+10)/(a²-1)²= 10(a²+1)/(a²-1)²
Похожие вопросы
Предмет: Английский язык,
автор: Lotas
Предмет: Русский язык,
автор: 123язь
Предмет: Қазақ тiлi,
автор: 00DocK00
Предмет: Алгебра,
автор: tatianapetelina
Предмет: Математика,
автор: триугольнык